2019
DOI: 10.1017/s0885715619000897
|View full text |Cite
|
Sign up to set email alerts
|

Structural dissymmetrization of optically anisotropic Grs64±1Adr36±1Sps2grandite from Meka Presedla (Kopaonik Mt., Serbia)

Abstract: In this paper, grandite core with Grs64±1Adr36±1Sps2 composition was crystallographically studied. This core represents zone A of the macroscopically visible five A–E zones of the optically anisotropic Grs58–64Adr36–42Sps2 grandite. The applied procedure includes the detailed analysis of the powder diffraction patterns, and the Rietveld refinements of the crystal structures in a series of 18 space groups and two mixtures, which were followed by the comparative analysis of the R-values, site occupancy factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Furthermore, it was previously shown that various tilting and orientations of the polyhedrons and polyhedral chains in other phosphate tungsten bronzes could derive the different space groups of crystallization [5], which makes this problem very complex from the structural aspect. The similar observations were also confirmed in our studies of other materials [38,39]. Although crystal structure refinements were beyond of the scope of this paper, different calculated crystallographic axis and angles between PWB, Li-PWB, and Ca-PWB (Table II) could be sufficient proof of the various tilting of their WO 6 octahedrons and PO 4 tetrahedrons.…”
Section: Connection Between Bronzes' Properties Catalytic Action and Br Reaction Responsesupporting
confidence: 86%
“…Furthermore, it was previously shown that various tilting and orientations of the polyhedrons and polyhedral chains in other phosphate tungsten bronzes could derive the different space groups of crystallization [5], which makes this problem very complex from the structural aspect. The similar observations were also confirmed in our studies of other materials [38,39]. Although crystal structure refinements were beyond of the scope of this paper, different calculated crystallographic axis and angles between PWB, Li-PWB, and Ca-PWB (Table II) could be sufficient proof of the various tilting of their WO 6 octahedrons and PO 4 tetrahedrons.…”
Section: Connection Between Bronzes' Properties Catalytic Action and Br Reaction Responsesupporting
confidence: 86%
“…It should be noted that low-symmetry birefringent garnets have been observed and studied previously (Shtukenberg et al , 2005; Frank-Kamenetskaya et al , 2007). A comprehensive review of the relevant literature was provided recently by Tančić et al (2020). However, nikmelnikovite is the first distinct garnet-supergroup member with a trigonal symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…(v) The option that various structural variations within the samples could take place Although the crystal structure refinements are beyond the scope of this paper, our previous studies of diverse mineral species and solid solutions, have demonstrated that the different UCPs, polyhedral distortions, site occupancy factors, bond lengths, bond angles and valence units, could be influenced either by: (1) different inserted cations into the mineral structure; and/or by ( 2) diverse conditions of their formation, in particular, the temperature and pressure (Tančić 2017(Tančić , 2018Tančić and Kremenović, 2022;Tančić et al, 2012Tančić et al, , 2020Tančić et al, , 2023.…”
Section: (Iii) Presence Of Other Phasesmentioning
confidence: 99%